Problems of Shariah governance framework and different bodies: an empirical investigation of Islamic banks in Bangladesh - Alam, Md. Kausar; Mustafa, Hasri; Uddin, Md. Salah; Islam, Md. Jahirul; Mohua, Marjea Jannat; Hassan, Md. Farjin (Korea Distribution Science Association, 2020)
The study aims to explore the problems of the existing Shariah Governance Framework (SGF) and its concerned authorities in the context of Bangladesh. Thus, according to responses from 17 respondents, this study outlines that Bangladesh has an absence of a shortage of experts, experienced, knowledgeable, and qualified Shariah people at all levels (i.e., the central bank, Islamic banks, Shariah Supervisory Boards (SSBs), and regulators). Therefore, Bangladesh does not have a separate Islamic banking act, Shariah audit firm, Shariah index institutions, and comprehensive SGF. The existing guideline has a limitation concerning its comprehensiveness, accountability, responsibility, and structure of SSBs. Islamic banks do not follow the instruction of the central bank in the formation of SSBs. As a result, there is an absence of competent and qualified SSB, which also results in the functions of Shariah departments as well as Shariah applications. Usually, the Board of Directors (BOD), management, executives, customers, and the public also have the conceptual gap about Islamic banks, SGF, and banking system compared to the regular prayers, faith, and belief. Concisely, Bangladesh requisites a comprehensive SGF, Islamic banking act, a standard accounting system, and a robust Shariah audit system for the overall development of Islamic banks and SGF.